Space-Air-Ground Integrated Network Architecture Based on Mobile Edge Computing - Jian WU; Min JIA; Qing GUO (天地一体化信息网络)
The next generation of wireless communication technologies will enhance the quality of user experience by supporting services such as intelligent transportation, intelligent healthcare, virtual/augmented reality, and more.These emerging services are typically computation-intensive and delay-sensitive, and must meet stringent delay, energy consumption, and reliability requirements that cloud-based services struggle to meet.In order to solve the above problems, mobile edge computing (MEC) technology was proposed to solve the problems of high latency and high bandwidth consumption when sending offloading requests back to the cloud computing centers.As an important research direction of 6G , space-air-ground integrated network (SAGIN) could make up for the huge coverage gap in the world, and had been widely concerned.This paper introduced MEC technology, federated learning technology and artificial intelligence technology into SAGIN to efficiently manage massive and heterogeneous resources in the network, and builded low-delay, low-energy consumption and high-reliability SAGIN to support various emerging services.